Pengembangan Game Edukasi Berbasis Android PADA Materi Jenis Konektivitas Internet Kelas X TKJ SMKN 1 Sepulu - Diana, Luluk Mauli; Wulandari, Ana Yuniasti Retno; Nilasari, Alfina Kusuma (Universitas Trunojoyo Madura, 2024)
The development of technology in the world of education can produce learning innovations, one of which is educational games. This study aims to develop an Android-based educational game application as a learning medium on the material of internet connectivity types for class X TKJ students at SMKN 1 Sepulu. This study uses the Research and Development (RD) method with the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. The results of the study indicate that this educational game application has succeeded in increasing the effectiveness of learning through validation testing and user trials. Validation by media experts obtained a percentage of 96.3% and material experts 98.4%, both in the